Perkembangan Kapitalisme Negara di Indonesia - Eric Hiariej (Jurnal Ilmu Sosial dan Ilmu Politik, 2006)
State capitalism in Indonesia has been experiencing significant transformation as control over financial resources no longer attainable. The decreasing role of the state as investor none the less, does not necessarily means the loosing commitment to perform as regulator